Investigation of the frequency and distribution of Pychiatric comorbidities in patients with Mastalgia - Dönmezdil, Süleyman; Araç, Eşref; Taş, İlhan; Yalçın, Murat; Tüzün, Abidin (Asian Journal of Medical Sciences, 2020)
Background: Mastalgia defines pain that is located in or felt in the breast area. Pain can be a symptom in many psychiatric disorders. Therefore, considering the psychiatric disorders in the evaluation of patients with mastalgia is of great importance in terms of treatment success and pain control Aims and Objective: In this study, we aimed to identify the psychiatric diagnoses that may be involved in the etiology of mastalgia and to retrospectively determine the frequency of patients who may need psychiatric treatment among the treatment options that can be used in patients with mastalgia Materials and Methods: We included patients who presented with breast pain between August 2017 and August 2018 and had normal results of radiological imaging studies. The archive system of the hospital was screened for the presence of any psychiatric admission before the diagnosis and previous psychiatric diagnoses, if any, were recorded Results: There were 1124 patients with mastalgia included in our study. Screening of psychiatric comorbidities recorded in the archive system revealed the presence of psychiatric admissions in 19.04% (n = 214) of the patients. Student's t-independent test showed a statistically significant difference between the mean age of mastalgia patients with and without psychiatric comorbidity Conclusion: In our study, we demonstrated the presence of anxiety disorder as psychiatric comorbidity in a high percentage of patients (43.9%), which was consistent with the rates reported in the literature of somatic symptoms, which are associated with anxiety disorder.